Bivalent antibody pliers inhibit β-tryptase by an allosteric mechanism dependent on the IgG hinge - Henry R. Maun (Nature Portfolio, 2020)
β-tryptases are responsible for most of the proteolytic activity during mast cell activation. Here, the authors develop β-tryptase-inhibiting antibodies and provide structural and biochemical evidence that the bivalency of the antibodies is a prerequisite for their inhibitory activity.